1974
DOI: 10.3109/00016347409157749
|View full text |Cite
|
Sign up to set email alerts
|

Cystine Aminopeptidase Activity in Pregnancy

Abstract: Abstracr. Maternal cystine aminopeptidase activity (CAP) and total urinary oestriol excretion have been compared in I I normal patients between 30 and 41 weeks gestation, in 9 patients with toxaemia of pregnancy and in 3 patients with a history of complication during the actual or previous pregnancy. The statistical correlation between maternal CAP and oestriol excretion in normal patients was poor (r=0.32). In patients with preeclampsia the results were as follows: low CAP levels generally were associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Even with careful urine collection the individual day-to-day Variation is rather pronounced (the coefficient of variations was 16% in the present study). Many reports also indicate that estriol assays not always reflect the condition of the feto-placental unit [6,15,19], and much research has during the last decade been directed towards new methods for evaluating the fetoplacental unit. In recent years much attention has been directed towards the determination of HCS äs a possible mean of monitoring the placental function [1,11,13,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with careful urine collection the individual day-to-day Variation is rather pronounced (the coefficient of variations was 16% in the present study). Many reports also indicate that estriol assays not always reflect the condition of the feto-placental unit [6,15,19], and much research has during the last decade been directed towards new methods for evaluating the fetoplacental unit. In recent years much attention has been directed towards the determination of HCS äs a possible mean of monitoring the placental function [1,11,13,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…CURZEN and VARMA [7] who compared CAP and urinary estriol assays concluded that CAP was of no value in predicting the condition of the feto-placental unit. Other authors [3,4,9,17,19,22] Comparative studies using all three parameters are scanty. KRISTENSEN et al [5] compared HCS, CAP and urinary estriol excretion in pregnancies complicated with essential hypertension and preeclampsia.…”
Section: Discussionmentioning
confidence: 99%